Recasting Recantation in 1540s England: Thomas Becon, Robert Wisdom, and Robert Crowley - Roddy, Kate (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
The legacy of John Foxe’s Acts and Monuments has urged scholars of the English Reformation to consider martyrdom the ultimate act of resistance, and recantation as an embarrassing lapse of faith. However, more recent criticism has drawn attention to the subversive potential of the false recantation, arguing that such events were not necessarily acts of capitulation but opportunities for covert evangelism and even shameless self-promotion. This article develops the above argument through an examination of the reformist Thomas Becon’s recantation of 1543, highlighting its innovative use of explicitly theatrical tropes to convey a message of falsity. However, the recantation’s potential for irony is shown to result in a lack of ideological stability in the narrative. Such instability, I argue, leads to further attempts to resolve or alter the meaning of a recantation through textual commentary. By means of close readings of the notable counter-recantation texts of Robert Wisdom and Robert Crowley, I demonstrate that the meaning of a recantation continues to be altered after the fact. Yet the defining quality of these texts is shown to be their confused and self-contradictory nature. I conclude that the continued argumentative oscillation of these texts indicates their ultimate failure to satisfactorily close down meaning and restore certainty to the co-religionist community.